Evaluation of Some Quality Parameters of Pumpkin Seeds and Oil After Roasting with Marjoram - Mariola Kozłowska; Małgorzata Ziarno; Katarzyna Zawada; Hanna Kowalska; Dorota Derewiaka; Małgorzata Chobot; Iwona Ścibisz (Foods)
Consumers include pumpkin seeds in their diet as a snack in raw form or minimally processed by roasting. This process enables the seeds to develop a characteristic aroma and color. Herbs and spices are also distinguished by a pleasant and delicate aroma. Among them, marjoram is particularly suited to drying, retaining its flavor better than other dried herbs. Marjoram can be used to impart flavor and aroma to food products and extend their shelf life because it can prevent lipid autoxidation. In this study, pumpkin seeds (Cucurbita pepo) were roasted with and without dried marjoram at 110 and 160 °C for 10 and 30 min, after which the oils were extracted. The results showed that with increasing temperature and roasting time, the moisture content and water activity of pumpkin seeds decreased. Furthermore, roasting pumpkin seeds with marjoram, particularly at 110 °C, enriched their aroma profile with terpenes characteristic of the marjoram aroma. Whether pumpkin seeds were roasted with or without marjoram, the fatty acid composition of the oils obtained was dominated by palmitic, stearic, oleic, and linoleic acids. However, the presence of marjoram during pumpkin seeds roasting resulted in lower peroxide values and specific extinction coefficients K232 and K270 in the oils obtained compared to their counterparts roasted without this spice. In addition, all the oils showed the ability to scavenge DPPH· radicals and were characterized by a higher proportion of yellow (positive value of the b* parameter) and green (negative value of the a* parameter) color. In comparison with the oil extracted from unroasted pumpkin seeds, the oil obtained after roasting exhibited a lower chlorophyll and a higher carotenoid content. Thus, roasting pumpkin seeds with spices may enrich their aroma profile with additional components, and the oils obtained may be characterized by better quality parameters.